The Influence of Learning Facilities on the Quality of Learning of Students Majoring in Office Management Automation - Sumarni Sumarni; Muh Darwis; Sitti Hardiyanti Arhas (Journal of Educational Development and Learning (JEDAL), 2025)
Learning facilities have a major role in improving the quality of learning. Adequate facilities can create conducive conditions for the learning process. This research was conducted to recognize the influence of learning facilities on the quality of learning. Research includes quantitative research by stating the relationship with causality. This study uses a population of 51 students majoring in Automation and Office Governance at SMK Negeri 4 Takalar. The methods used in data collection are observation, documentation and questionnaire techniques. For analysis techniques, descriptive statistical analysis techniques are used, using percentages and inferential statistical analysis techniques with data normality tests, product-moment correlation analysis, and simple linear regression analysis. The test showed that the results in the form of indicators from the Learning Facilities variable were in the very good category, while the Learning Quality variable was classified as good. According to the results of the product-moment correlation test, there was an influence between the two variables with a correlation coefficient value of 0.992. Based on the results of simple linear regression analysis, it can be concluded that there is a significant influence of learning facilities on the quality of learning in students majoring in Automation and Office Governance at SMK Negeri 4 Takalar.